Job seekers have more suitable job opportunities in decarbonization in the Global North than in the Global South - Shi Zhao; Quan Shao; Lei Zhang; Xia Zhou; Huaming Guo; Zhifu Mi (Communications Earth & Environment)
Abstract A just transition to green economy sectors must be grounded in optimizing job matching, that is, suitable opportunities of aligning employers with job seekers, which is critical for meeting a zero-emissions future. However, the interaction between job matching and emission patterns remains unclear. Here we examine both historical and future trends in this interaction using a global unifying explanation with high-aggregated model. Our findings reveal national-level latitude and wealth effects. In high-latitude regions, 79% of job matching in relatively wealthy nations show a positive correlation with emissions reductions. In contrast, this trend is observed in only 10% of poorer nations located at low latitudes. Introducing the Shared Socioeconomic Pathways, our projection shows global job matching will be consistently improved under SSP1-2.6, but only nations in Asia, the Middle East, and Africa will benefit under SSP5-8.5. This work provides a quantitative perspective to plan the low-carbon transition of global labor force.